Effects of shape, location and quantity of the joint on bending properties of laminated bamboo lumber. (10th January 2020) - Lin, Qiuqin; Huang, Yuxiang; Li, Xinde; Yu, Wenji
Highlights: Hook joint was the most suitable type of joint for production of large-scaled LBL. The joint located at 1/4 of sample length had little effect on bending properties. The bending strength decreased significantly with increasing the joint quantities. Abstract: Large-scaled laminated bamboo lumber (LBL) is manufactured from bamboo strips after lengthening with joints. In this study, three types of joint shapes for lengthening bamboo strips were explored with three-layered LBL, and the effects of quantities and locations on bending performance of the LBL were further evaluated. The heat-treated (120 °C) moso bamboo strips with joints were used to produce the laminated samples, comparing with the control group without joints. The results showed that the reduced rate of bending strength of LBL with three types joints were all exceed 10%. However, the simpler and more efficient process of machining and gluing made hook joint the most potential choice for bamboo strip lengthening. Based on optimizing joint shape, the reduced rate of strength attained minimum (1.43%) when the hook joint was located at the 1/4 length of the sample. As increasing the joint quantity from 1 to 3, the bending strength decreased by 6.82–31.11%. It appeared that the parameters of joint had a great influence on the strength of LBL and it is important to control the quantities and locations of the joint.